TPACK: Analysis of Biology Learning Outcomes at Senior High School Level`s in the Bandar Lampung City During Online Learning - Dina Maulina; Ismi Rakhmawati; Arwin Surbakti; Darlen Sikumbang; Dwi Wahyudi (Jurusan Pendidikan Biologi - Universitas Siliwangi, 2021)
The purpose of this study was to analyze students' biology learning outcomes towards the achievement of basic competencies in biology materials at senior high school and to evaluate the implementation of online biology learning for teachers and students in order to achieve the expected competencies. The research design used an ex post facto design, with the population being all state senior high school students in the city of Bandar Lampung in a different distribution of sub-district locations represented based on the equivalent level of school accreditation. Samples were taken from a population consisting of: SMA N 2 Bandar Lampung, SMA N 5 Bandar Lampung, and SMA N 7 Bandar Lampung. The acquisition of quantitative data in the form of learning outcomes values on the subject matter of plantae, qualitative data in the form of analysis of the results of a questionnaire intended for teachers and students. Interviews were conducted to obtain secondary data in the form of descriptive data carried out by teleconference. The result showed that there was a significant difference in learning outcomes in online classes compared to face-to-face classes (p 0.05). The dominant online learning application used is using google classroom which is already based on the Learning Management System (LMS). As many as 74.1% of students stated that online learning limits interaction and communication with friends and teachers regarding subject matter. Therefore, the results of this study prove that the biology learning outcomes of students carried out online based on LMS have a significant effect, but the interaction, collaboration and communication between students during the learning process become an obstacle.